Relationship Of Serum Hemoglobin And Vitamin D Levels With Posutral Balance - Ngestiningsih, Dwi; Wicaksono, Maulana Akbar; Wicaksono, Muhammad Agung Wibowo; Probosuseno, Probosuseno; Supatmo, Yuswo; Rachmawati, Banundari (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background: The population of the elderly in Indonesia has increased significantly in recent years. The incidence of falls is influenced by postural balance. Vitamin D and hemoglobin deficiency are associated with decreased muscle function and postural balance. This study is to investigate the relationship between vitamin D and hemoglobin levels with postural balance in the elderly. Methods: The study used a cross-sectional design with the participation of 33 patients (aged 64.94±5.42 years). The study sample was elderly individuals who fulfilled the inclusion criteria at Semarang Elderly Posyandu. Patients performed postural balance test, with Sharpened romberg and tandem gait test. The examination of vitamin D and hemoglobin was taken from the patient's venous blood. Vitamin D was measured using ELISA. Results: The results of the independent sample t-test analytic test revealed a P value of vitamin D (0.007) and a P value of hemoglobin of (0.021) (p<0.05). There is a meaningful relationship between vitamin D and hemoglobin levels with postural balance in the elderly.. Conclusion: Decreasing Haemoglobine and Vitamin D impair the postural balance.